A Qualitative Study of the Latter Effects of the COVID-19 Pandemic on Patients Living With Chronic Pain - Eleni Hapidou PhD, C.Psych; Victoria Borg Debono PhD; Saxon Schwarz BSc; Jennifer Anthonypillai BSc (Journal of Patient Experience, 2023)
This qualitative study examined the effects of the COVID-19 pandemic on the lives of patients living with chronic pain (CP). Patients referred to an interdisciplinary pain management program between July and December of 2021 were asked to respond to the question: “How did the COVID-19 pandemic affect your life?” Fifty-four patients provided comments in response to this question. The comments were analyzed using an inductive approach. Ten themes emerged: (1) psychological state, (2) limitations on social life and activities, (3) minimal to no effect, (4) beliefs and opinions associated with COVID-19, (5) family dynamics, (6) healthcare disruptions, (7) pandemic-related fear, (8) changes in work, (9) change in pain, and (10) getting COVID-19. These themes mirror those found during the onset of the pandemic, with the addition of theme #4. Themes demonstrate the challenges experienced by individuals living with CP, in addition to new developments in the latter portion of the COVID-19 pandemic. It is important to understand the ramifications of shutdowns, so we are better able to address issues that occur in their aftermath.